DISTRIBUSI POISSON DAN DISTRIBUSI EKSPONENSIAL DALAM PROSES STOKASTIK - Sugito, Sugito; Mukid, Moch Abdul (MEDIA STATISTIKA, 2011)
In the queueing system, the processes usually come from a Poisson process. In this system should be obtained an arrival distribution and a service distribution. This paper studies about the form of the number of arrival distribution, the number of service distribution, the interarrival distribution and the service time distribution. Futhermore it talks about the relation of them to a Poisson distribution andÂ  an exponential distribution. Â  Keywords: Poisson Process, Poisson Distribution, Eksponential Distribution